Mouse count - Walsh, Ellen Stoll (San Diego : Harcourt Brace, 1991)
Presents a counting story in which ten little mice must work together to free themselves after they are caught by a fortunately greedy snake.
"Voyager Books."
Notable/Best Books (A.L.A.)
School Library Journal starred
Wilson's Children
2.0
K-3
Keywords: Counting; Mice -- Fiction; Snakes -- Fiction; Counting; Mice -- Fiction; Snakes -- Fiction